Overcoming Hazards of E-commerce Recommender Systems for Social Good - Kathriarachchi E; Alam S; Rashid MS (Association for Computing Machinery, 2026)
Recommender systems used on e-commerce websites (e-commerce RS) are crucial to enhance the online shopping experiences of customers and improve business performance. Despite ongoing enhancements in their effectiveness, e-commerce RS face challenges that could harm customers, businesses, and society. Addressing these challenges effectively is crucial to protecting the interests of stakeholders relying on e-commerce RS. Proposed strategies include developing technical solutions, increasing customer awareness, and enacting relevant laws and regulations. However, current research has not yet thoroughly examined these solutions in a unified manner. This review fills that gap by providing a detailed overview of the hazards associated with e-commerce product recommendations and the measures implemented to mitigate these hazards. The paper assesses these solutions within the context of existing research, emphasizing their implications and suggesting future directions to improve the safety and efficacy of e-commerce RS.
Keywords: Information systems; information retrieval; retrieval tasks and goals; recommender systems; product recommendations; risks and hazards; solutions